Phoneme recognition for speech theraphy system using Hidden Markov Model Toolkit (HTK) - Nazriah Mahmud, 1988-, author; Sheikh Hussain Shaikh Salleh, 1958-, supervisor; Fakulti Biosains dan Kejuruteraan Perubatan (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2011)
Project Paper (Sarjana Muda Kejuruteraan (Bio - Perubatan)) - Universiti Teknologi Malaysia, 2011